Apparent longitudinal relaxation of mobile spins in thin, periodically excited slices - Gädke, Achim; Nestle, Nikolaus (Diffusion Fundamentals, 2005)
In this contribution, we present simulations and first experimental results on the apparent longitudinal relaxation behavior of mobile spins in thin periodically excited slices. This phenomenon is especially of interest in the context of NMR microimaging at extremely high spatial resolution and also for the development of mechanically detected NMR on biological samples under semiambient conditions. In the most simple case, the signal amplitude available in such an experiment is determined by the recovery of saturated in-slice magnetization during the time interval between two excitations. This magnetization recovery results both from relaxation and from diffusive exchange with magnetization outside the slice. We recently studied the combined effect of relaxation and diffusion in a simple saturation-recovery experiment on a fully relaxed sample. In the case of periodic excitation, the diffusion balance is complicated by the fact that there is also partially excited out-of-slice magnetization left over from earlier excitation cycles.